Corporate Governance Model in the Malaysian Tourism Small and Medium-Sized Enterprises - Mohd Shariff, Nurhazani; Zainol Abidin, Azlan; Bahar, Mohd Roslee (Advances in Social Sciences Research Journal, 2018)
To ensure Tourism Small and Medium-Sized Enterprises (TSMEs) in Malaysia continue to support the national tourism industry and remain a source of employment to the community, the government has focused on determining the key success factors of Malaysian TSMEs’ performance with a focus on tourism entrepreneurs’ motivation and management. Hence, the primary objective of the study is to develop a model of best practice for corporate governance in the Malaysian TSMEs. The findings highlight nine corporate governance practices significantly derived as important component for the TSMEs namely shareholders, top management, board of directors, ownership and board structure, conflict of interest, stakeholders, social responsibility, remuneration and transparency. Based on these findings, a conceptual model has been developed to present a standard practice for corporate governance in the Malaysian TSMEs. These practices play vital role in managing the TSMEs toward achieving their strategies and objectives. The model contributes to the better and successful management of TSMEs particularly since corporate governance has proven as vital aspect for SMEs growth. It is suggested that further research should be conducted to investigate the significance of these practices to the successful management of the TSMEs.